Sieve of A. Selberg in the algebraic number fields - Levin, B.; Tuliaganova, M. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. В. Левин, М. И. Туляганова. Решето А. Сельберга в алгебраических числовых поляхB. Levinas, M. Tuliaganova. A. Selbergo rėtis algebrinių skaičių kūnuose